Etika Komunikasi Remaja Di Dusun III Padang Sari Jorong Limau Puruik Kecamatan Kinali Kabupaten Pasaman Barat - Karisma Wulandari; Yusuf Afandi (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This research is based on looking at the ethics of adolescent communication with older people, where communication as a process of exchanging messages from communicators to communicants requires ethics as something that is used as a view and guideline to measure the good and bad deeds according to a habit in society. Communication ethics can be seen from the form of ethics starting a conversation, face-to-face communication and communication techniques used. This type of research is using descriptive qualitative research methods that describe what is about an event. In this study, the author describes the ethical use of adolescent communication focused on older people in Dusun III Padang Sari Jorong Limau Puruik, Kinali District, West Pasaman Regency. In collecting data, the authors used observation, interview and documentation techniques with informants related to the application of communication ethics between adolescents and older people in Dusun III Padang Sari.The results of the study were the use of adolescent communication ethics in hamlet III Padang Sari Jorong Limau Puruik, Kinali District, West Pasaman Regency which focused on communication ethics with older people, consisting of communication ethics in starting conversations, teenagers rarely saw the condition of the prospective interlocutor, second, friendly teenagers. and polite to the interlocutor depending on the level of familiarity, third, listening, teenagers are not good at listening especially when given advice. While the ethics of face-to- face communication, first, stay with the other person, teenagers tend to not focus and glance left and right, second, keep the intonation and speed of speech, teenagers use high intonation, the three teenagers often ask questions in the form of asking how they are. The communication technique used by adolescents when communicating with older people is to confirm when they feel they have misunderstood and pay less attention to non-verbal communication well, such as not bowing when walking in front of older people